Evaluation of new American Academy of Pediatrics guideline for febrile urinary tract infection - Da Min Choi; Tae Hoon Heo; Hyung Eun Yim; Kee Hwan Yoo (Korean Pediatric Society, 2015)
PurposeTo evaluate the practical applications of the diagnosis algorithms recommended by the American Academy of Pediatrics urinary tract infection (UTI) guideline.MethodsWe retrospectively reviewed the medical records of febrile UTI patients aged between 2 and 24 months. The patients were divided into 3 groups: group I (patients with positive urine culture and urinalysis findings), group II (those with positive urine culture but negative urinalysis findings), and group III (those with negative urine culture but positive urinalysis findings). Clinical, laboratory, and imaging results were analyzed and compared between the groups.ResultsA total of 300 children were enrolled. The serum C-reactive protein level was lower in children in group II than in those in groups I and III (P<0.05). Children in group I showed a higher frequency of hydronephrosis than those in groups II and III (P<0.05). However, the frequencies of acute pyelonephritis (APN), vesicoureteral reflux (VUR), renal scar, and UTI recurrence were not different between the groups. In group I, recurrence of UTI and presence of APN were associated with the incidence of VUR (recurrence vs. no recurrence: 40% vs.11.4%; APN vs. no APN: 23.3% vs. 9.2%; P<0.05). The incidence of VUR and APN was not related to the presence of hydronephrosis.ConclusionUTI in febrile children cannot be ruled out solely on the basis of positive urinalysis or urine culture findings. Recurrence of UTI and presence of APN may be reasonable indicators of the presence of VUR.